PERMUDAH LAYANAN DAN PERLUASAN PASAR MELALUI PEMANFAATAN TEKNOLOGI DIGITAL PADA UMKM UHAT KLB MALANG - Haya Nur Safa'atin; Andika Wulan Febriani; Agung Winarno; Agus Hermawan (Jurnal Pemantik, 2022)
The purpose of helping UMKM UHAT KLB is to expand market share, facilitate online transactions, change the mindset of UMKM UHAT KLB, related to the use of digital technology. The purpose of the assistance to the UMKM Uhat KLB is because many consumers buy tofu through the wheat KLB website, so we provide deeper assistance to take advantage of digital technology. This study uses the active participation method of mentoring, namely discussion, mentoring, training, and monitoring. So, the results of the research are the application of digital technology, for example, making a brand logo by utilizing technology, where the brand logo is used as a characteristic of what KLB and as a differentiator for other tofu competitors. The second is Instagram social media, which can expand the market share of UMKM Uhat KLB. In addition, the use of omnichannel and Go Mart also makes it easier to order what KLB products. Next, that is changing the mindset of the owners and employees of what KLB that the distribution of tofu is not only through traditional markets in Malang. However, by utilizing digital technology, UMKM Uhat KLB can market its products digitally